Does It Matter to Establish a Strategic Partnership for COVID-19 Prevention and Control? The Perspective of Multiple Distances in Emerging Economies - Zhao, Can; Wei, Meng-Yang; Chen, Yan; Shen, Ruo-Yan (Frontiers in Public Health, 2022)
The rapid spread of the COVID-19 pandemic in early 2020 has impacted the politics, economy and society of countries around the world. The public health diplomacy system through which developed countries in Europe and America used to provide vertical one-way assistance to developing countries faces huge challenges. How emerging economies can cooperate to fight the pandemic on the basis of mutual trust and mutual benefit has become an urgent issue. In this paper, we examine the impact of political mutual trust on the effectiveness of pandemic prevention and control from the perspective of establishing strategic partnerships between emerging economies. Furthermore, taking into account the huge differences between emerging economies, this paper explores institutional distance, cultural distance, and geographical distance—the adjustment effect of the control effect. Studies have shown that the improvement of political mutual trust is conducive to the formation of a community of shared futures between countries and has a positive effect on curbing the spread of the pandemic. The increase of the three-dimensional distance of institutions, culture, and geography will weaken the effect of establishing strategic partners for pandemic prevention and control. This paper explores a new model of horizontal international cooperation among emerging economies, and provides a reference for emerging economies to deal with common globalization issues in the future.